Involuntary Psychiatric Commitment in the Era of COVID-19: Systemic Social Oppression and Discourses of Risk in Public Health and Bioethics - Sara M. Bergstresser (International Journal of Critical Diversity Studies, 2021)
This paper considers the continuation of involuntary psychiatric hospitalization during the COVID-19 pandemic, with a focus on the United States of America. Situating psychiatric diagnosis and hospitalization within the broader context of decades of social and historical research, as well as emergent fields such as feminist philosophy of disability, critical diversity studies (CDS), and mad studies, I argue that a socially mediated process which is legitimated with appeals to “health” and “safety” should not be maintained during a pandemic of a readily communicable virus that is especially dangerous for individuals clustered in inpatient settings. A CDS approach allows the clear identification of “severe mental illness” as a marked category of social difference which leads to multiple forms of social oppression. In this paper, I show how involuntary psychiatric hospitalization is a social process through which marked individuals are dehumanized and confined. Furthermore, I consider why the maintenance of the status quo, even under pandemic conditions, demonstrates that involuntary treatment is primarily a political, rather than a medical, process. Finally, I outline why the politics of involuntary treatment should concern longstanding disciplines such as public health and bioethics, as well as emergent disciplines like CDS.